Gorbachev’s USSR - Ra'anan, Uri. author. aut Link
XXI, 154 p.
Keywords: A collection of papers presented at Boston University by leading Sovietologists evaluating the meaning of developments in the USSR and their impact since Gorbachev became head of government. The consensus is that the USSR is facing a systemic crisis, affecting ideology, leadership and economics.